Intercultural Communication Competence in Overcoming the Culture Shock of Migrant Workers in Japan - Muhajirin, Muhajirin; Tessa Shasrini (LPPM Institut Studi Islam Sunan Doe, 2023)
Japan is known as a developed country that has advanced technology, and is a civilized country, so it is not uncommon for Indonesian people to want to become Indonesian Migrant Workers (TKI) in Japan because of the large amount of royalty they are given. However, in this way, it is necessary to make adjustments made by TKI in communicating in Japan or scientifically it is usually called intercultural communication. This study aims to determine the competence of intercultural communication carried out by TKI in Japan in dealing with culture shock. This study uses a qualitative descriptive research type, data analysis techniques in the form of observation, interviews, and documentation. Data analysis techniques are carried out through data reduction and drawing conclusions. This research was conducted through interviews with Indonesian migrant workers in Japan. The results showed that Indonesian migrant workers were very interested in working in Japan because they were paid high wages. Japan is known as a country that has good manners, culture shock that occurs, namely difficulties in language and seasons. With so TKI continue to try to adapt. In addition, Indonesian TKI also take a deep self-approach to their surroundings and try to join the new environment.